Structural Behavior of Confined Concrete Filled Aluminum Tubular (CFT) Columns under Concentric Load (Journal of Engineering, 2016)
This paper introduces an experimental study on the behavior of confined concrete filled aluminum tubular (CFT) column to improve strength design, ductility and durability of concrete composite structures under concentrically loaded in compression to failure. To achieve this: seven column specimens with same concrete diameter 100mm and without steel reinforcement have been examined through experimental testing, which are used to study the effects of the thickness of the aluminum tube encased concrete ( thickness : 0mm, 2mm, 3mm, 4mm and 5mm with same length of column 450mm), length of column (thickness 5mm and length of column 700mm) and durability (thickness 5mm and length of column 450mm) on the structural behavior of  (CFT) columns.It is concluded from this work that the compression force capacity is affected by thicknesses of the aluminum tube with respect to reference specimen. Where the used of aluminum tube thicknesses in column specimens led to increased in load carrying capacity in range (16% for C2 -224% for C5 ). The specimen has a length of 700mm with 5mm thickness the decreased of strength was 0.06% than the specimen with 5mm thickness and length 450mm. For slender column the overall buckling was observed while the local buckling for the short column is the dominant failure shape. Regarding durability, no apparent difference has been found between the structural behavior of the specimen that immersed in aggressive solution and specimen in air. Keywords: circular, column, aluminum, CFT, conﬁnement